2013
DOI: 10.1080/19440049.2013.766766
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new tadalafil analogue found in a dietary supplement

Abstract: A new tadalafil analogue, acetaminotadalafil, was detected by HPLC in a bulk powder that is being used as an ingredient formanufacturing dietary supplements. The analogue was isolated by semi-preparative HPLC. A chemical structure of the new compound was elucidated by HPLC, LC-quadrupole time-of-flight mass spectrometry (LC-Q-TOF/MS), nuclear magnetic resonance (NMR), infrared (IR) and circular dichroism (CD) spectroscopy. The compound was identified as an acetylatedcompound of aminotadalafil. The structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Adulteration is an exemplary repercussion of such laxity. Well documented are instances of diuretics, stimulants, anorectics, or oxidative uncouplers contained in weight loss supplements [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], steroids in performance enhancers [75][76][77][78][79][80], and phosphodiesterase 5 inhibitors contained within male enhancement products [72,74,[81][82][83][84][85][86][87][88][89][90][91][92][93]. At least nine people died in Sweden following exposure to Kratom adulterated with Odesmethyltramadol, a potent opioid analgesic.…”
Section: Supplement Regulationmentioning
confidence: 99%
“…Adulteration is an exemplary repercussion of such laxity. Well documented are instances of diuretics, stimulants, anorectics, or oxidative uncouplers contained in weight loss supplements [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], steroids in performance enhancers [75][76][77][78][79][80], and phosphodiesterase 5 inhibitors contained within male enhancement products [72,74,[81][82][83][84][85][86][87][88][89][90][91][92][93]. At least nine people died in Sweden following exposure to Kratom adulterated with Odesmethyltramadol, a potent opioid analgesic.…”
Section: Supplement Regulationmentioning
confidence: 99%
“…Since the identification of homosildenafil by Shin et al [7], there are 46 analogues being reported [5]. Recently, our laboratory found a new tadalafil analogue, acetaminotadalafil, in dietary supplement [8]. The consumption of these adulterated products could be harmful to consumers with various health risks.…”
Section: Introductionmentioning
confidence: 97%
“…Several analogs of tadalafil have been reported in the literature . Aminotadalafil ( RR ‐ATDF) was first described in 2006 .…”
mentioning
confidence: 99%